The Effects of Dividend Taxes on Equity Prices : A Re-examination of the 1997 U.K. Tax Reform - Bond, Stephen (IMF Working Papers; Working Paper ;, 2007)
We re-examine the extent to which personal taxes on dividends are capitalized into the equity prices of domestic firms, using data from around the time of the 1997 U.K. dividend tax reform, which removed a significant tax credit for an important group of investors: U.K. pension funds. The tax-adjusted CAPM suggests that the impact should depend on an average of dividend tax rates across all investors, and that U.K. pension funds should reduce their holdings of the previously tax-favored asset: U.K. equities. Given that U.K. pension funds are small relative to the total size of the world capital market, a small open economy-type argument implies that the main effect of the reform would be to reduce U.K. pension funds' ownership of U.K. equities, with little impact on their price. We present evidence which is consistent with these hypotheses. We discuss why previous research (Bell and Jenkinson, 2002) reached a different conclusion.